St Kilda: quarries, fields and prehistoric agriculture - Fleming, Andrew; Edmonds, Mark (Proceedings of the Society of Antiquaries of Scotland, 2000)
On the western side of Village Bay, on the island of Hirta in the St Kilda archipelago, there are extensive dolerite quarries for the extraction of stone for production of `flaked stone bars' or hoe-blades, which are closely comparable to similar tools found in Neolithic and Bronze Age contexts in the Northern Isles. Broken hoe-blades are widely distributed among the walls and buildings of the village abandoned in 1930. Their use was probably coeval with that of irregular walled field systems in Village Bay and Gleann Mór. A viable community evidently occupied Hirta well before the Iron Age. These findings suggest that current views of the prehistory of Hirta and of the role of agriculture in the island's history should be revised.